Optimization of The Electrospinning Process for Preparation of Nanofibers From Poly (Vinyl Alcohol) (PVA) and Chromolaena odorata L. Extrac (COE) (Department of Physics, Faculty of Mathematics and Natural Sciences, 2020)
The Cromaloena odorata (COE) contains phenols, flavonoids, tannins, alkaloids, saponins, steroids that possess diverse therapeutic effects. However, COE has poor solubility in water and poor absorbtion in the body. Incorporation of COE in nanofiber system is a promising way to increase CEO solubility. One of the method to produce nanofiber is electrospinning. The electrospinning process there are three of the most important process parameters are applied flowrate, voltage and TCD. In this study we developed optimized condition for electrospinning process of polyvinyl alcohol (PVA)/CEO and their characterization. The Scanning electron microscopy (SEM) analysis showed that modification of flowrate and TCD did not affect the morphology of PVA and COE fiber. However fiber diameter decreased when lower flowrate, higher voltage was applied, and TCD. Fourier Transform Infrared (FTIR) study was conducted to identify possible intermolecular interaction between PVA/COE that has potential application as antimicrobial wound dressing.